Study of Cure Kinetics of Vinyl-tri(phenylethynyl)silane Monomer - Tan, Dexin; Wang, Yanli; Xing, Honglong; Li, Zhong (Asian Journal of Chemistry, 2013)
An isothermal cure kinetics of vinyl-tri(phenylethynyl)silane ((ph-C=C)3-Si-C=CH2) (VTPES) was investigated by differential scanning calorimetry in the temperature range 345-370 ºC. The results showed that the shapes of the conversion curves were all similar and all of the cure reactions could be described by an autocatalytic kinetic model.